Pengaruh Elemen Fraud Hexagon terhadap Kecurangan Akuntansi Pada Badan Usaha Milik Desa di Kabupaten Buleleng - I Made Gede Diana Putra; Nyoman Ayu Wulan Trisna Dewi (Jurnal Ilmiah Akuntansi dan Humanika, 2022)
This study aims to determine the effect of the fraud hexagon element on accounting fraud at BUMDes in Buleleng Regency. This type of research is quantitative research. The population used is 124 BUMDes employees consisting of the chairman, secretary and treasurer. The sampling technique in this study used purposive sampling method using a sample of 72 BUMDes employees. Data were obtained from distributing questionnaires to respondents which were then measured using a Likert scale. Analysis of the data used in this study using descriptive statistical analysis, data quality test, classical assumption test and multiple linear analysis using SPSS 24. The results of this study state (1) pressure (compensation suitability) has a negative and significant effect on accounting fraud, (2 ) capability (competence) has a negative and significant effect on accounting fraud, (3) the opportunity for the internal control system to have a negative and significant effect on accounting fraud, (4) rationalization (individual morality) has no effect on accounting fraud, (5) ego (leadership style) has a negative and significant effect on accounting fraud and (6) collusion (unethical behavior) has a positive and significant effect on accounting fraud.have met the criteria.